Pemberdayaan Ekonomi Kreatif Dan UMKM Melalui Digitalisasi Di Kabupaten Gowa - Mutmainnah, Inayatul; Utomo, Jepri (Jurnal Pengabdian Masyarakat Bhinneka, 2022)
Empowerment of the creative economy and Micro, Small and Medium Enterprises is an activity that can be carried out to improve the economic welfare of the people in Gowa Regency, especially for business actors. Digitization efforts are applied as a means of improvement. The empowerment process is carried out with the socialization method, namely by conveying aspects of legal digitization and economic digitalization aspects. This activity was attended by 18 target participants from 18 sub-districts in Gowa Regency, and 1 participant representing each sub-district. Each participant is a youth in the youth category who represents and is sent from each sub-district. This empowerment is useful for participants in understanding and understanding the implementation of legal digitization by establishing and registering business entities, registering Intellectual Property Rights online, and registering business licenses online. In addition, increasing motivation by participating in online trainings, conducting online marketing strategies in various social media and marketplaces, getting business success tips on official websites from the government and digitalization media.